Tax Avoidance Determinants with Sales Growth as Moderator: Penentu Penghindaran Pajak dengan Pertumbuhan Penjualan sebagai Moderator - Ernandi, Herman; Prasetya, Atina Nabila Ade (Indonesian Journal of Law and Economics Review, 2025)
Background: Tax avoidance remains a strategic decision frequently undertaken by firms to manage financial pressure and maintain performance stability. Specific Background: Prior studies show inconsistent findings regarding the role of leverage and company size, while the contribution of sales growth as a moderating variable remains underexplored. Gap: Limited empirical evidence integrates sales performance dynamics into the tax avoidance model within consumer non-cyclical firms. Aim: This study examines the effect of leverage and company size on tax avoidance and evaluates the moderating role of sales growth. Results: Findings show that leverage significantly increases tax avoidance, while company size also contributes positively. Sales growth strengthens the relationship between leverage and tax avoidance, indicating that firms with stronger sales tend to utilize tax minimization strategies more aggressively. Novelty: The study introduces sales growth as a contextual moderator to clarify inconsistencies in previous findings. Implications: Results provide insights for managers and policymakers in designing governance mechanisms to ensure tax compliance, particularly in firms with high debt levels and strong market performance. Highlights:• Leverage and firm size significantly shape tax avoidance• Sales growth strengthens leverage–tax avoidance relationship• Model clarifies inconsistencies in previous tax avoidance studies Keywords: Tax Avoidance, Leverage, Firm Size, Sales Growth, Moderation Model